HUBUNGAN ADEKUASI HEMODIALISIS DENGAN STATUS GIZI PASIEN PENYAKIT GINJAL KRONIS YANG MENJALANI HEMODIALISIS REGULER - Ajeng Sulistianing Utami; I Gede Yasa Asmara; Deasy Irawati (Faculty of Medicine Universitas Mataram, 2021)
Background: The quality of hemodialysis (HD) is one of the predictor factors of mortality and morbidity in patients with CKD 5. Increasing the adequacy of hemodialysis that can be evaluated from dosage’s sufficiency and effectivity, also can reduce the risk of having complications and side effects to certain organs. One of the complications that can be appeared is malnutrition. The aim of this research is to study the correlation between hemodialysis adequacy with CKD stage 5 patient’s nutritional status. Method: This research was held on August until September 2020 in Hemodialysis Unit of RSUD Kota Mataram. The research was a cross-sectional approach. There were 51 sample that are fit the inclusion and exclusion criterias. The data collection was done by recording the patients medical records. HD adequacy was assessed by patient's Kt/V and nutritional status was assessed by BMI parameter and patient's serum albumin level. The correlation test that was used in this research is Spearman correlation test to determine the correlation between variables. Result: In this research, sample’s mean age was 55,1 years old with 51% male and 49% female. The analysis correlation that was determined by using Spearman correlation test showed that, the correlation between HD adequacy and patient’s BMI was p=0.967 and r=0.006 and the correlation between HD adequacy and patient’s serum albumin level was p=0.662 and r=0.063. Conclusion: There was no significant correlation between HD adequacy and patient’s nutritional status. Key Words: Chronic Kidney Disease, Hemodialysis Adequacy, Nutritional Status, Body Mass Index, Serum Albumin Level